IoT Based Omni-Channel Consumer Conformity in Fashion Industry: Do Gender, Age, Monthly Income Still Matter? - Elfindah Princes; Idris Gautama So (International Journal of Organizational Business Excellence, 2021)
The research aimed to examine the influence of socioeconomic characteristics (age, gender, and income) on consumer conformity during the Internet of Things. A 7 items instrument using 7-likert scale for dimensions of consumer conformity in fashion industry for fashion consumers in Indonesia aged between 18 – 55 years old. Data analysis was performed on 470 responses using ANOVA Three-Way Test to find out if the socioeconomic characteristics are significant to the components of consumer conformity in fashion industry. This is considered the first research examining the influences of socioeconomic characteristics to Consumer Conformity. The results reveal that among the three characteristics, only age is found to be significant to Consumer Conformity. Therefore, to support the Consumer Conformity in fashion consumers, the marketer should pay attention to each age groups.